Mechanical Energy and Its Relationship with Some Kinematical Variables and Scoring Accuracy Indicator in Youth Soccer Players - Jabbar, Nadhim (Journal of Physical Education, 2020)
The research aimed at identifying the mechanical, motor, and potential energy values as well as for kinematical variables, scoring accuracy indicator values in youth soccer players. In addition to that, the research aimed at identifying the relationship between the mechanical, motor, and potential energy values, kinematical variables, scoring accuracy indicator values in youth soccer players. The researcher used the descriptive method on (7) youth players from Newroz youth soccer club. He used (2) specialized video cameras for analyses and programing using Kinovea. He also conducted scoring accuracy to collect the data that was treated using SPSS. Five views were used from a total of six makings (35) for analyzing mechanical variables and scoring accuracy to conclude a relationship between mechanical, motor, and potential energy with many variables. Finally, he recommended that coaches should pay attention to mechanical and motion energy for their direct relationship with working muscle group development.